2015
DOI: 10.1002/adom.201500284
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon‐Assisted Indirect Light Absorption Engineering in Small Transition Metal Catalyst Nanoparticles

Abstract: Light absorption in plasmonic nanoantennas constitutes an interesting way of enhancing catalytic reactions occurring at surfaces of metals nanoparticles by forming hot electron–hole pairs. These can either directly transfer to empty orbitals of adsorbed species on the nanoparticle surface or thermalize via electron–phonon coupling and enhance reaction rates via a photothermal reaction channel. While this scheme, in principle, can be efficient for the well‐known plasmonic materials Ag and Au due to their large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…A natural implication of this hypothesis is that plasmonic nanomaterials can be tuned in such a way that under illumination they will selectively enhance particular chemical pathways (those which are activated by the particular electronic transitions supported by plasmon-induced local fields) while suppressing other chemical pathways. One way to achieve this objective might be to combine plasmonic particles with more active metals in a single catalyst 35 36 or have bimetallic nanoparticles that combine a plasmonic metal core and a more chemically reactive metal shell. In these systems, the interaction of the chemically reactive metal with adsorbates allows for tuning of the electronic structure of adsorbates on the nanoparticle (based on the selection of the metal), while the optical properties are governed by the plasmonic metal.…”
Section: Discussionmentioning
confidence: 99%
“…A natural implication of this hypothesis is that plasmonic nanomaterials can be tuned in such a way that under illumination they will selectively enhance particular chemical pathways (those which are activated by the particular electronic transitions supported by plasmon-induced local fields) while suppressing other chemical pathways. One way to achieve this objective might be to combine plasmonic particles with more active metals in a single catalyst 35 36 or have bimetallic nanoparticles that combine a plasmonic metal core and a more chemically reactive metal shell. In these systems, the interaction of the chemically reactive metal with adsorbates allows for tuning of the electronic structure of adsorbates on the nanoparticle (based on the selection of the metal), while the optical properties are governed by the plasmonic metal.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing transition metal nanoparticle size redshifts optical absorption, but it increases cost and reduces surface area, and therefore catalytic activity. Recently, it has been shown that plasmonic nanoparticles can be used to increase optical absorption in adjacent nanoparticles (19)(20)(21)(22), for instance, enabling hydrogen detection (23,24).Previous reports of photocatalytic transformation in plasmonic metal nanoparticle systems rely on the metal to double as both the Significance Plasmon-enhanced photocatalysis holds significant promise for controlling chemical reaction rates and outcomes. Unfortunately, traditional plasmonic metals have limited surface chemistry, while conventional catalysts are poor optical absorbers.…”
mentioning
confidence: 99%
“…Increasing transition metal nanoparticle size redshifts optical absorption, but it increases cost and reduces surface area, and therefore catalytic activity. Recently, it has been shown that plasmonic nanoparticles can be used to increase optical absorption in adjacent nanoparticles (19)(20)(21)(22), for instance, enabling hydrogen detection (23,24).…”
mentioning
confidence: 99%
“…For example, Antosiewicz et al demonstrated the use of lithographically fabricated Ag nanodisks as light antennae to enhance the optical absorption power in Pd QSMNPs with sizes of less than 5 nm. 58 It is worth pointing out that the Pd QSMNPs and the antenna Ag nanodisks have to be well separated by electrically insulating dielectric materials to avoid the charge exchange between them. Without the appropriate dielectric separation, the light absorption in the Pd QSMNPs cannot benefit from the enhanced surface electric fields of the Ag nanodisks.…”
Section: Hot-electron-driven Surface Chemistry Of Qsmnpsmentioning
confidence: 99%